Recent Trends on the Use of Nanoparticles for Nitric Oxide Delivery in Antimicrobial Applications - Hasan, Sayeed; Thomas, Nicky; Thierry, Benjamin; Vreugde, Sarah; Wormald, Peter-John; A. Prestidge, Clive (Drug Delivery Letters, 2016)
Nitric oxide (NO) has a multitude of biological activities and has great potential for numerous therapeutic applications. However, its small size, short halflife and instability under physiological conditions make achieving therapeutic levels challenging. Nanoparticle carriers offer potential to overcome the various physiochemical and biological challenges for effective NO delivery. State of the art in the development and application of nanoparticle based carrier systems for the encapsulation and delivery of NO and NO-precursor molecules are critically reviewed. Specific focus is directed to the antimicrobial performance of NO delivered by polymeric, inorganic and lipid based- nanocarriers. NO-precursor molecules have been identified as effective approaches for NO delivery. Liposomes, silica particles, hydrogels and polymeric nanoparticles offer specific properties and performance to overcome the NO delivery challenges and have demonstrated enhanced therapeutic efficacy; some mechanistic insight is given. Specific antimicrobial and infected wound healing applications of NO-nanocarriers are highlighted and these show significant promise for translation to clinical application. Polymeric, inorganic and lipid based- nanocarriers are effective encapsulation and delivery systems for NO-precursors. Prospects for NO delivery in the treatment of infectious diseases and wound care management are evident.
Keywords: Anti-microbial